2021
DOI: 10.3390/s21248501
|View full text |Cite
|
Sign up to set email alerts
|

LightAnomalyNet: A Lightweight Framework for Efficient Abnormal Behavior Detection

Abstract: The continuous development of intelligent video surveillance systems has increased the demand for enhanced vision-based methods of automated detection of anomalies within various behaviors found in video scenes. Several methods have appeared in the literature that detect different anomalies by using the details of motion features associated with different actions. To enable the efficient detection of anomalies, alongside characterizing the specificities involved in features related to each behavior, the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, studies have shown that lowering the number of convolution layers has a significant impact on network performance; see, for example, [45,46]. Furthermore, limiting the number of convolution layers also has a significant impact on network performance in terms of computation efficiency [47,48]. Therefore, inspired by previous works [43,47], this study explored the relationship between network depth and its performance specifically using the HAM10000 dataset.…”
Section: Shortening the Architecturementioning
confidence: 98%
“…On the other hand, studies have shown that lowering the number of convolution layers has a significant impact on network performance; see, for example, [45,46]. Furthermore, limiting the number of convolution layers also has a significant impact on network performance in terms of computation efficiency [47,48]. Therefore, inspired by previous works [43,47], this study explored the relationship between network depth and its performance specifically using the HAM10000 dataset.…”
Section: Shortening the Architecturementioning
confidence: 98%
“…So, it is important to propose lightweight models that can work well with limited resource devices like mobile devices. Some possible solutions have been proposed by [100][101][102]. 9.…”
Section: Lightweight Modelsmentioning
confidence: 99%
“…Interestingly, a work efficiently discussed abnormal behavior detection [13]. In this work, the authors created LightAnomalyNet as a lightweight framework using 3D CNN of the DL algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Also, the false positive rate (FPR) is the ratio between FP and the sum of FP and TN and it is represented as Equation (13).…”
Section: Identification Approach Has Suspicious Action Does Not Have ...mentioning
confidence: 99%